IMPROVING THE STUDENTS’ ENGLISH READING COMPREHENSION BY USING RANDOM TEXT STRATEGY AT THE TENTH GRADES STUDENTS OF MAS DARUL QUR’AN - Saruris Sihombing, Jati (Faculty of Tarbiyah nad Teacher Training, 2021)
This research conducted to know the improvement of the students’ reading comprehension by using Random Text Strategy at the tenth grades students of MAS Darul Qur’an. In this research consist of three meetings in two cycles. There are two kinds of data in this research, namely quantitative data and qualitative data. Whereas, the quantitative data taken from each test given by the researcher to the students during the study. Then the qualitative data taken from the observation sheet, field notes, interview and the last is documentation that has been collected by researcher during the research. Based on the data showed that there an improvement on the students reading comprehension in each test. In pre-test, there were only 36,11% (13 students) who can answer the question well. In post-test one, there was 63,88% (23 students) who success the test. While, in post-test 2 there was 86,11% (31 students) who success the test. It was concluded that the students’ scoreimproved every cycle. From the result of the observation, interview, field notes and documentation that has been analyzed, it can be concluded that the students more active and the learning process more effective. The students pay close attention to the researcher when explaining the material in front of the class. Random Text Strategy could improve the students’ reading comprehension at the X Grade MAS Darul Qur’an, where it was can showed from the result of the research.Keywords: Reading, Reading Comprehension, Random Text Strategy